The Effect of Elderly Fitness on Cholesterol Levels - Annisa Nur Nazmi; Yahya Afisena; Anita Dwi Ariyani (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Hypercholesterolemia is a disease that often attacks the elderly due to plaques sticking to the walls of blood vessels, resulting in blockage of blood vessels (atherosclerosis). One of the non-pharmacological treatments to treat hypercholesterolemia is fitness exercise. This study aims to determine the effect of fitness exercise on changes in cholesterol levels in the elderly at the Apel Posyandu in the Work Area of ​​the Sobo Banyuwangi Public Health Center in 2019. This research method is quasi-experimental and uses a pre-experimental research design in the form of a